2010
DOI: 10.1146/annurev.micro.112408.134211
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Microcompartments

Abstract: Bacterial microcompartments (BMCs) are organelles composed entirely of protein. They promote specific metabolic processes by encapsulating and colocalizing enzymes with their substrates and cofactors, by protecting vulnerable enzymes in a defined microenvironment, and by sequestering toxic or volatile intermediates. Prototypes of the BMCs are the carboxysomes of autotrophic bacteria. However, structures of similar polyhedral shape are being discovered in an ever-increasing number of heterotrophic bacteria, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
328
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 319 publications
(333 citation statements)
references
References 67 publications
4
328
0
1
Order By: Relevance
“…The latter compound moves from the MCP to the cytoplasm, where it enters central metabolism, providing energy and/or carbon for cell growth. In the case of the carboxysome, sequestration allows the concentration of CO 2 to be elevated in the immediate vicinity of RuBisCO, improving its catalytic efficiency (13,16,18). For other MCPs, sequestration helps to balance the production and consumption of the toxic/volatile catabolic intermediate.…”
Section: Essential Features Of Bacterial Microcompartments Mcps Are Umentioning
confidence: 99%
See 4 more Smart Citations
“…The latter compound moves from the MCP to the cytoplasm, where it enters central metabolism, providing energy and/or carbon for cell growth. In the case of the carboxysome, sequestration allows the concentration of CO 2 to be elevated in the immediate vicinity of RuBisCO, improving its catalytic efficiency (13,16,18). For other MCPs, sequestration helps to balance the production and consumption of the toxic/volatile catabolic intermediate.…”
Section: Essential Features Of Bacterial Microcompartments Mcps Are Umentioning
confidence: 99%
“…Multiple MCP types are often found within a single genome, except for carboxysomes, where only one type (␣ or ␤) is found per genome (20). Several studies have suggested that MCP loci are subject to frequent horizontal gene transfer, including recent comprehensive analyses of sequenced genomes (6,13,20,28,29). In many cases, MCPs are encoded by large operons that include multiple MCP shell protein paralogs along with MCP-associated enzymes.…”
Section: Mcp Distribution and Ecologymentioning
confidence: 99%
See 3 more Smart Citations